Частиномовна специфіка атрибутивних синтаксем - Гандзюк, Олександра Михайлівна; Handzyuk, O.M. (Brno, 2004)
The article is devoted to the investigation of the secondary predicative syntaxems and as one of their variants the attributive suntaxems are analised. In the given investigation the part of speech specificity of attributive syntaxems is presented.
Keywords: частина мови; синтаксема; атрибутивна синтаксема